Acrocephalosyndactyly Syndrome: A Rare Case Report - Satya Ranjan Misra (Indian Journal of Forensic Medicine & Toxicology, 2021)
Acrocephalosyndactyly or Apert syndrome is a rare disorder in which the fingers and toes are fused,giving the appearance of webbed hand and feet. Also, there is craniosynostosis, leading to severe mid-facehypoplasia and characteristic facial deformities. Here there is a genetic mutation in the fibroblast growthfactor receptor 2 (FGFR2) gene with autosomal dominant inheritance. A case of an 8-year-old male child isreported here with frontal bossing, acrocephaly, prominent ocular hypertelorism with divergent strabismus,saddle-shaped nose, mid-face hypoplasia, crowded anterior teeth, sparse hair and severe bilateral syndactylyof the feet and hands.